Unveil the Gold – Revealing Metal Threads and Decorative Materials of Early Twentieth Century Traditional Chinese Children's Hats. (18th August 2021) - Cheung, Angela; Solazzo, Caroline; Tsui, Wai-shan
ABSTRACT: This paper presents the study of metal threads and other decorative materials on 11 traditional Chinese children's hats dated to the early twentieth century. The lavishly decorated hats were presented to children to protect them from evil and bless them for good health and fortune. Those hats were selected for display in the 2015 exhibition ' Wearable Blessings: Traditional Chinese Children's Clothing ' at the Hong Kong Heritage Museum (HKHM). In addition to the conservation work, the hats were fully studied to encompass analysis of the materials and understand the craftsmanship of the exquisitely decorated hats. In particular, various forms of metal threads were identified. The majority of the threads were revealed to be 'membrane threads', mostly gold or silver lamellae on leather substrates and are used in the hats as flat strips or foils. Among the 11 hats, nine are also decorated with metal-wrapped threads with fibrous cores (silk, linen, or cotton). The base substrate of the membrane thread was identified as either sheep or goat skin by means of proteomics in 11 samples tested from six hats. These findings coincide with the information recorded in an ancient Chinese encyclopaedia ' Chinese Technology in the Seventeenth Century '. Using proteomics, we also found a collagen signal matching to a fish species, Larimichthys crocea or large yellow croaker that is suspected to come from the glue binding the metal onto the base substrate. Other than the metal threads, feathers were also identified by microscopic examination on one of the hats. In terms of craftsmanship, leather gold embroideries and the hidden framework of a three-dimensional lotus ornament were examined and revealed by X-radiography respectively. This study demonstrates that the integration of scientific analysis with conservation is valuable in the investigation of material culture and intricate craftsmanship of historical objects.